LncRNA FAM13A-AS1 Promotes Renal Carcinoma Tumorigenesis Through Sponging miR-141-3p to Upregulate NEK6 Expression - Wang, Xin Jun; Li, Si; Fang, Jiang; Yan, Zhi Jian; Luo, Guang Cheng (Frontiers in Molecular Biosciences, 2022)
Long non-coding RNAs are a diverse catalog of RNAs that have been implicated in various aspects of tumorigenesis. Emerging evidence indicates that they play crucial roles in tumor growth, disease progression, and drug resistance. However, the clinical significance of lncRNAs in tumor behavior prediction and disease prognosis as well as the underlying mechanism in renal cell carcinoma (RCC) remains elusive. By analyzing the gene expression profiles of 539 RCC patients from the TCGA cohort and 40 RCC patients from an independent cohort, we identified FAM13A-AS1, a poorly studied lncRNA, upregulated in RCC patients. Knockdown experiments revealed that FAM13A-AS1 promotes cell proliferation, migration, and invasion by interacting with miR-141-3p. FAM13A-AS1 regulates the expression of Nek4 by decoying miR-326. In addition, there was a strong positive correlation between the expression of FAM13A-AS1 and NEK6 in RCC patients. In summary, our results demonstrate the oncogenic role of FAM13A-AS1 in RCC and suggest that it promotes tumorigenesis by upregulating the expression of NEK6 by competitively binding to miR-141-3p.